Epidemiology and Molecular Characterization of Bacteremia Due to Carbapenem‐Resistant Klebsiella pneumoniae in Transplant Recipients. Issue 10 (6th September 2013) - Clancy, C. J.; Chen, L.; Shields, R. K.; Zhao, Y.; Cheng, S.; Chavda, K. D.; Hao, B.; Hong, J. H.; Doi, Y.; Kwak, E. J.; Silveira, F. P.; Abdel‐Massih, R.; et al.
Abstract: We conducted a retrospective study of 17 transplant recipients with carbapenem‐resistant Klebsiella pneumoniae bacteremia, and described epidemiology, clinical characteristics and strain genotypes. Eighty‐eight percent (15/17) of patients were liver or intestinal transplant recipients. Outcomes were death due to septic shock (18%), cure (24%) and persistent (>7 days) or recurrent bacteremia (29% each). Thirty‐ and 90‐day mortality was 18% and 47%, respectively. Patients who were cured received at least one active antimicrobial agent and underwent source control interventions. Forty‐one percent (7/17) of patients had intra‐abdominal infections; all except one developed persistent/recurrent bacteremia despite drainage. Two patients tolerated persistent bacteremia for >300 days. All patients except one were infected with sequence type 258 (ST258), K. pneumoniae carbapenemase (KPC)‐2‐producing strains harboring a mutant ompK35 porin gene; the exception was infected with an ST37, KPC‐3‐producing strain. Seventy‐one percent (12/17) of patients were infected with ST258 ompK36 mutant strains. In two patients, persistent bacteremia was caused by two strains with different ompK36 genotypes. Three ompK36 mutations were associated with significantly higher carbapenem minimum inhibitory concentrations than wild‐type ompK36 . Pulse‐field gel electrophoresis identified a single ST258 lineage; serial strains from individual patients were indistinguishable. In conclusion, KPC‐ K. pneumoniae bacteremia exhibited highly diverse clinical courses following transplantation, and was caused by clonal ST258 strains with different ompK36 genotypes. Abstract : This study describes long‐term outcomes of organ transplant recipients with bacteremia due to carbapenem‐resistant Klebsiella pneumoniae and evaluates the genetic profiles of infecting strains.